Spanish Validation of the Brief Pornography Screen Within a Clinical Sample of Individuals with Gambling Disorder - Tarragón, Ernesto; Testa, Giulia; Granero, Roser; Potenza, Marc; Kraus, Shane; Uríszar, Juan Carlos; Chiclana Actis, Carlos; Fernández-Aranda, Fernando; Jiménez-Murcia, Susana; Mestre-Bach, Gemma (Archives of Sexual Behavior, 2025)
Problematic pornography use (PPU) shares characteristics with behavioral addictions, such as gambling disorder (GD), and PPU and GD may frequently co-occur. In order to fll existing gaps in screening instruments for PPU validated in GD, the study examined the psychometric properties of the Spanish version of the Brief Pornography Screen (BPS) within a clinical sample of individuals with GD. A total of 200 individuals seeking treatment for GD were consecutively recruited. The psychometric properties of the BPS were examined by performing confrmatory factor analysis (CFA) and testing for evidence of convergent and discriminant validity. The CFA supported a one-factor solution showing high internal consistency (α=0.81). The BPS showed convergent validity and correlated with psychological distress, general psychopathology, impulsive tendencies, and low self-directedness. The BPS demonstrated adequate psychometric properties and is therefore recommended as a brief screening tool for identifying probable PPU in individuals seeking treatment for GD.
Keywords: Gambling disorder; Problematic pornography use; Compulsive sexual behavior disorder; Scopus; WOS; JCR